TINJAUAN HUKUM ISLAM TERHADAP PRAKTIK JUAL BELI NANAS DENGAN SISTEM TEBAS: Studi Kasus Desa Kasomalang, Kabupaten Subang, Jawa Barat - Samsul Bahri; Irvan Iswandi; Ali Aminulloh (Melati Institute, 2023)
Buying and selling and farming is one of the commodities of Indonesian society. Especially in rural areas, such as the Kasomalang village community. On average, the people of Kasomalang village earn as farmers. such as rice, vegetables and fruits. The majority of farmers in Kasomalang village grow pineapples, because the area is very suitable for planting pineapples because the area has not too hot weather and is highland. The purpose of this study was to find out the practice of buying and selling with the Tebas system in Kasomalang village and to find out the review of Islamic law on the practice of buying and selling pineapples with the Tebas system in Kasomalang village. The method used in this research is qualitative research. The approach taken in this research is empirical juridical, namely legal research regarding the enforcement or implementation of legal provisions. The data sources in this study are primary data sources and secondary data sources. Data collection techniques through observation, interviews, and documentation. The results of the study are: 1) The practice of buying and selling pineapple slashing systems in Kosamalang Village, Subang, West Java, uses an oral contract, after the contract has occurred, the slasher gives a down payment, then the payment will be made when the pineapple is ready to be harvested. This has become the custom of the village. 2) The sale and purchase of pineapples in Kosamalang Village, Subang, West Java, is reviewed in terms of Islamic law, the sale and purchase is valid because it meets the pillars and conditions of the sale and purchase, namely in the second contract where the object of the sale and purchase is clear in terms of shape, and the agreed price.